ARTISTIC INTERPRETATION OF THE THEME OF THE BATTLE OF KRUTY IN UKRAINIAN POETRY - Kyyaschenko, M. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is an attempt to give a complex evaluation of the poetry dedicated to the Battle of Kruty that is an example of the Ukrainian literature of the resistance of the beginning of the XX-th century as a periodic phenomenon of the Ukrainian literary process of the Soviet period in connection with Ukrainian literary traditions, the present and the future epochs; the poetic personalities and texts are analyzed.